2020
DOI: 10.1002/ajim.23185
|View full text |Cite
|
Sign up to set email alerts
|

Occupational buckwheat allergy as a cause of allergic rhinitis, asthma, contact urticaria and anaphylaxis—An emerging problem in food‐handling occupations?

Abstract: Buckwheat is a known, though uncommon, allergen in occupational settings. It has recently gained popularity as healthy food and as an ingredient in gluten-free diets. We describe a series of six patient cases with occupational immediate allergy to buckwheat. Three cooks, two bakers, and a worker in a grocery store were occupationally exposed to buckwheat flour and developed immediate allergy to buckwheat, which was confirmed by skin prick testing and measurement of specific immunoglobulin E antibodies. Four of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It can be trigger by irritants, drugs, hormonal imbalance, pregnancy, age, and others or have the idiopathic character, which is generally called the non-allergic, non-infectious rhinitis) ( Hellings et al, 2017 ; Mullol et al, 2020 ). Rhinitis caused by allergens and mediated by IgE is called allergic rhinitis (AR) ( Passali et al, 2018 ; Jungewelter et al, 2020 ). Additionally, some of the anatomical abnormalities, presence of foreign bodies in the upper airways, nasal polyps, primary ciliary dyskinesia can be manifested in the same way, therefore rhinitis demand a careful diagnosis ( Hellings et al, 2017 ; Dykewicz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be trigger by irritants, drugs, hormonal imbalance, pregnancy, age, and others or have the idiopathic character, which is generally called the non-allergic, non-infectious rhinitis) ( Hellings et al, 2017 ; Mullol et al, 2020 ). Rhinitis caused by allergens and mediated by IgE is called allergic rhinitis (AR) ( Passali et al, 2018 ; Jungewelter et al, 2020 ). Additionally, some of the anatomical abnormalities, presence of foreign bodies in the upper airways, nasal polyps, primary ciliary dyskinesia can be manifested in the same way, therefore rhinitis demand a careful diagnosis ( Hellings et al, 2017 ; Dykewicz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, it is important to recognize that contemporary baking work may expose bakers to unusual allergens such as psyllium or buckwheat 1 and to consider all these allergens when a work‐related disease is suspected in a baker.…”
Section: Discussionmentioning
confidence: 99%
“…Baker's rhinitis and asthma caused by inhaled cereal flours are among the most common occupational diseases. Lately, gluten‐free or vegan diets have increased in popularity and bakers' allergens are changing in parallel 1 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was a well-recognized relationship between sensitization to airborne molds and allergy to mushrooms ingestion [50]. In another clinical study of a series of six patient cases with immediate occupational allergy (allergic rhinitis, asthma, and urticaria) to buckwheat, it has been revealed that patients had anaphylaxis after ingestion of food that contained buckwheat [51].…”
Section: Co-influence Of Respiratory and Food Allergiesmentioning
confidence: 99%